A Rare Cause of Lower Abdomen Pain – Primary Urinary Bladder Amyloidosis - Parmar, Kalpesh; Thakur, Abhishek; Rajiv Ranjan, Kumar; Kumar, Santosh (Annals of Pathology and Laboratory Medicine, 2021)
Primary urinary bladder amyloidosis is a rare disease. Its importance lies in the ability of the disease to masquerade the carcinoma urinary bladder in clinical presentation and imaging but with a distinctively contrasting treatment. The commonest presentation is painless hematuria. Definitive diagnosis is made on histopathology and by ruling out systemic amyloidosis. Here, we report a 60-year-old male presenting with lower abdomen pain diagnosed with primary urinary bladder amyloidosis and discuss the management based on current literature.